Chloroform Extract of Artemisia annua L. Relaxes Mouse Airway Smooth Muscle. (12th November 2017) - Huang, Jun; Ma, Li-Qun; Yang, Yongle; Wen, Nana; Zhou, Wan; Cai, Congli; Liu, Qing-hua; Shen, Jinhua
Abstract : Artemisia annua L. belongs to the Asteraceae family, which is indigenous to China. It has valuable pharmacological properties, such as antimalarial, anti-inflammatory, and anticancer properties. However, whether it possesses antiasthma properties is unknown. In the current study, chloroform extract of Artemisia annua L. (CEAA) was prepared, and we found that CEAA completely eliminated acetylcholine (ACh) or high K + -elicited (80 mM) contractions of mouse tracheal rings (TRs). Patch-clamp technique and ion channel blockers were employed to explore the underlying mechanisms of the relaxant effect of CEAA. In whole-cell current recording, CEAA almost fully abolished voltage-dependent Ca 2+ channel (VDCC) currents and markedly enhanced large conductance Ca 2+ -activated K + (BK) channel currents on airway smooth muscle cells (ASMCs). In single channel current recording, CEAA increased the opening probability but had no effect on the single channel conductance of BK channels. However, under paxilline-preincubated (a selective BK channel blocker) conditions, CEAA only slightly increased BK channel currents. These results indicate that CEAA may contain active components with potent antiasthma activity. The abolished VDCCs by CEAA may mainly contribute to the underlying mechanism through which it acts as an effective antiasthmatic compound, but the enhanced BK currents might play a less important role in the antiasthmatic effects.